Revenue targeting in fisheries - Nguyen, Quang (2014)
We apply the target revenue model, a version of prospect theory, to investigate how fishermen adjust their trip length to changes in daily revenue. The key finding is that certain groups of fishermen seem more likely to behave according to the target revenue model rather than to the standard model of labor supply. We also find that vessel capacity has little effect on whether the captains seek target revenue. The study strongly supports the integration of prospect theory into the framework of labor supply analysis.